СРАВНИТЕЛЬНАЯ ХАРАКТЕРИСТИКА КОМПОНЕНТОВ В ПАРАХ IIIB-III ПО ДАННЫМ НАБЛЮДЕНИЙ НА РАДИОТЕЛЕСКОПЕ УРАН-2 - Браженко, А. И.; Мельник, В. Н.; Коноваленко, А. А.; Доровский, В. В.; Ващишин, Р. В.; Французенко, А. В.; Рукер, Г. (Одеські астрономічні публікації, 2011)
In this paper we analyze the properties of type IIIb and type III bursts in IIIb-III pairs observed by radio telescope URAN-2 at frequencies 16-32 MHz. We discuss pro and contra of harmonic phenomenon of decameter IIIb-III pairs.